P095 Epigenetic clocks have the potential to predict future grip strength in males but not females. (23rd April 2022) - Fuggle, Nicholas R; Westbury, Leo; Reswan, Faisal; Graham, Nikki; Kitaba, Negusse; Ward, Kate A; Ward, Kate A; Harvey, Nicholas; Holloway, John; Dennison, Elaine; Cooper, Cyrus
Abstract: Background/Aims: Sarcopenia and muscle ageing are associated with substantial morbidity and mortality for the individual and significant costs to healthcare budgets. However, if we can identify those at particular risk of muscle decline it may be possible to intervene, prevent further deterioration and improve the musculoskeletal health of the ageing population. DNA methylation accumulates across the lifecourse and provides the basis for biological clocks, generating a measure of age acceleration (i.e. that an individual is biologically older or younger than their chronological age would suggest). An example is the GrimAge clock which was designed to estimate remaining longevity and thus may potentially represent a novel risk marker for muscle deterioration. We aimed to investigate whether there is an association between methylation-measured age acceleration and future grip strength in a group of community-dwelling older adults. Methods: This study is based within the Hertfordshire Cohort Study. At baseline, participants attended research visits where health-related questionnaires were completed and blood samples were collected. DNA was extracted from peripheral blood leukocytes and DNA methylation at CpG sites was measured using the Infinium Human Methylation Beadchip arrays (Illumina Inc., San Diego, CA) (450k, n = 99 and 850k, n = 326). After pre-processing, GrimAge epigenetic age acceleration was measured, using the array-specific publicly available algorithms, and standardised to an SD scale. Grip strength was ascertained using the JAMAR dynamometer at baseline and follow-up. Linear regression was used to examine GrimAge acceleration in relation to grip strength at baseline and follow-up in unadjusted models and those adjusted for age, height and BMI. Results: A total of 425 participants (213 males and 212 females) were included in our analyses. The mean age at baseline was 64.1 years (SD 2.6) for males and 65.9 years (SD 2.7) for females. The median follow-up time was 11.6 years (IQR 11.0-12.4) and mean GrimAge at baseline was 58.4 years (SD 5.6). Higher GrimAge acceleration was significantly associated with lower grip strength at baseline (β= -1.43kg [95% CI: -2.39, -0.47] per SD greater age acceleration in univariate model, p < 0.01) in unadjusted and adjusted models and at follow-up (β= -1.25kg [-2.24, -0.26] per SD, p < 0.02). No significant associations were observed in females. Conclusion: Our results suggest that greater GrimAge acceleration, as a measure of biological age acceleration, is significantly associated with lower grip strength after approximately a decade of follow-up. However, this association was only observed in males and not in females. The GrimAge clock was designed using methylation surrogates of age-related plasma proteins and smoking pack years, and it may be that the variation in these was more marked in our male population compared to females. Further work is required to investigate and replicate the above association. Disclosure: N.R. Fuggle: None. L. Westbury: None. F. Reswan: None. N. Graham: None. N. Kitaba: None. K.A. Ward: None. K.A. Ward: None. N. Harvey: None. J. Holloway: None. E. Dennison: None. C. Cooper: None.